Evaluation of surface integrity in turning operations of fly ash geopolymer using taguchi method - Jasim, Zaydoun Farhoud (School of Manufacturing Engineering, 2019)
The scope in this research starts with using the geopolymer based on fly ash material to be experimented after preparing the synthesis which can give the required mechanical properties, therefore many specimens with different concentration of NaOH has been prepared, also some of them has been processed through Cold-Press machine in order to reduce the porosity. For machining requirements, the factors feed rate, cutting speed and depth of cut has been examined. CHEVALIER model FCL-608 lathe machine has been selected as turning machine because of its capability. Additionally, the cutting tool's material has experimented with two types of cutting tools, one of them is Cubic Boron Nitride (CBN) and the other is Cemented Carbide. The results of experiment have been evaluated based on the value of surface roughness to measure the surface quality of final product using MITUTOYO F-300 machine at MPU3. Taguchi method used as the design of experiment DOE to obtain an orthogonal array and calculate the signal-to-noise (S/N) ratio. The analysis of variance (ANOVA) it is harnessed to obtain the cutting characteristics by identifying the best combination of machining parameters and the most significant parameter affect the surface integrity.